Challenges In Developing Of Vocational Madrasa Based On Foster Father - Erna Nurkholida (Ri'ayah: Jurnal Sosial dan Keagamaan, 2018)
This paper described the challenges and changes in developing vocational madrasa, foster father program and the role of Nahdatul Ulama, By using descriptive qualitative research, it provided the portray of the development of vocational madrasa, the early born of Madrasah Kejuruan Maslahiyah Badas Kediri. The findings showed that students in choosing a school took interests 85%, majors 80%, and the last is experience 25%. The variable of motivation, the most dominant factor influence is conducive learning environment was 86 %, desire was 85 %, and activities in learning was 80 %. The interview of the respondents stated that they were under Nahdatul Ulama organisation but it did not give so much help in developing it. They built by themself or swadaya and they stated that NU should be a bridge in buliding network with the corporations